2011
DOI: 10.1590/s1676-06032011000200025
|View full text |Cite
|
Sign up to set email alerts
|

Riqueza de borboletas em dois parques urbanos de Curitiba, Paraná, Brasil

Abstract: Abstract:In order to contribute to the knowledge of butterflies of Curitiba, were studied two urban municipal parks, the Botanical Garden which has total area of 178,000 m² and has a grove of preserved Araucaria forest only for scientific research, and the Municipal Park of Barreirinha which has total area of 275,380 m² and the area used for sampling of free access to population, with predominance of reforested vegetation. After 10 months of sampling, totaling 240 hours, 787 individuals and 166 species were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
1
1
1
3
Order By: Relevance
“…The richness of butterfly species in the Atlantic Forest region of the Fernão Dias Environmental Protection Area was higher than that observed in some studies (RITTER et al, 2011;BORDIN et al, 2019;BERTINOTI et al, 2020;SILVA et al, 2020) and lower than that reported in others (BONFANTTI et al, 2011;BELLAVER et al, 2012;VIEIRA et al, 2020). Nevertheless, results were within the expected range for forest regions in Brazil, given the differences in the size of experimental sites, sampling methods and efforts between studies.…”
Section: Discussioncontrasting
confidence: 50%
“…The richness of butterfly species in the Atlantic Forest region of the Fernão Dias Environmental Protection Area was higher than that observed in some studies (RITTER et al, 2011;BORDIN et al, 2019;BERTINOTI et al, 2020;SILVA et al, 2020) and lower than that reported in others (BONFANTTI et al, 2011;BELLAVER et al, 2012;VIEIRA et al, 2020). Nevertheless, results were within the expected range for forest regions in Brazil, given the differences in the size of experimental sites, sampling methods and efforts between studies.…”
Section: Discussioncontrasting
confidence: 50%
“…Em Porto Alegre, Ruszczyk (1986a) registrou 43 espécies de borboletas ao longo das principais avenidas da cidade. Bonfantti et al (2011) registraram 166 espécies em dois parque urbanos na cidade de Curitiba. Já na capital mineira, Silva et al (2007) realizaram um estudo em uma mata urbana registrando 91 espécies de borboletas, o que corresponde a 18,7% da lepidopterofauna conhecida para Belo Horizonte (Brown & Freitas 2000a).…”
Section: Resultsunclassified
“…Em trabalho realizado por Pereira et al (2015), em remanescente urbano de Floresta Ombrófila Mista no município de Curitiba-PR, onde foram realizadas amostragens em duas áreas, sendo que em uma delas não foram amostrados nenhum representante da família Riodinidae, corroborando o presente trabalho. Em outros levantamentos realizados em áreas semelhantes como Cordeiro e Richardo (2018) no município de Pinhão-PR e Bonfantti et al (2011) no município de Curitiba-PR, representatividade das famílias Riodinidae e Lycaenidae foram inferiores a 10%.…”
Section: Resultsunclassified
“…Em ambientes estáveis, ou seja, sem a degradação da flora, são encontradas em qualquer época do ano (BROWN e FREITAS, 1999;ACCACIO et al, 2011). Também contribui o fato de serem de fácil observação e de terem taxonomia bem conhecida (BROWN, 1991;FREITAS et al, 2003).…”
Section: Introductionunclassified